Nonclinical Parameters Affecting Primary Cesarean Rates in the United States - Haberman, Shoshana; Saraf, Sumit; Zhang, Jun; Landy, Helain J.; Branch, D. W.; Burkman, Ronald; Gregory, Kimberly D.; Ramirez, Mildred M.; Bailit, Jennifer L.; Gonzalez-Quintero, Victor H.; Hibbard, Judith U.; Hoffman, Matthew K.; Kominiarek, Michelle; Lu, Li; Van Veldhuisen, Paul; Von Gruenigen, Vivian; null (American Journal of Perinatology, 2014)
Objective Cesarean is the single most common operation in United States and has reached epidemic proportions in recent decades. Our objective was to study the effect of nonclinical parameters on primary cesarean rates in a large contemporary population.Study Design We designed a retrospective multicenter study using data obtained from electronic medical records from 19 U.S. hospitals between 2005 and 2007 (Consortium on Safe Labor Database), which included 145,764 term, singleton, nonanomalous, vertex, live births that included labor. The impact of nonclinical parameters (patient and provider characteristics, time of delivery, institutional policies, and insurance type) was investigated using modified Poisson regression methodology and classification and regression tree analysis.Results There were 125,517 vaginal and 20,247 cesarean deliveries. Using the multivariable model, the nonclinical parameters with statistical significance for primary cesarean were delivery during evening hours, a male provider, public insurance, and nonwhite race (p < 0.001).Conclusions Cesarean rates are associated with several nonclinical factors. Further investigation into these factors might help to develop strategies to reduce their influence and hence the rates of cesarean.
Keywords: cesarean section rates; nonclinical factors; physician factors